Review of structural neuroimaging in patients with refractory obsessive-compulsive disorder - Atmaca, Murad (Springer, 2011)
The notion that some special brain regions may be involved in the pathogenesis of obsessive-compulsive disorder (OCD) dates back to the beginning of the twentieth century. Structural neuroimaging studies in the past 2 decades have revealed important findings that facilitate understanding of OCD pathogenesis. Current knowledge based on functional and structural neuroimaging investigations largely emphasizes abnormalities in fronto-striatal-thalamic-cortical and orbitofronto-striato-thalamic circuits in the pathophysiology of OCD. However, these neuroimaging studies did not focus on refractory OCD. The present review mainly focused on structural neuroimaging performed in OCD, which had been ignored previously, and highlighted current evidence supporting that orbito-frontal cortex and thalamus are key brain regions, and that the hippocampus-amygdala complex is associated with refractoriness to the available treatment strategies. However, to fully reveal the neuroanatomy of refractoriness, longitudinal studies with larger samples are required.
Keywords: structural neuroimaging; refractory; obsessive-compulsive disorder; orbito-frontal cortex; thalamus